(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2026)
This article analyses the “Voces Tobas” project, which focuses on documenting, disseminating and promoting the Toba/Qom language in contemporary contexts where signs of linguistic displacement are evident. In an scenery where the intergenerational transmission of Toba/Qom is declining, this initiative conceives of the production of podcasts and animated videos as a linguistic activism strategy, aimed at creating new species for the circulation of oral tradition, based on a participatory methodology and in collaboration with leaders of a Toba/Qom people. The podcast format, in particular, allows the Toba/Qom language to reach a broad audience, both within and outside the community, and promotes its linguistic and cultural dissemination thanks to the use of open-access digital platforms. Furthermore, the materials designed and disseminated on the YouTube channel ‘Voces Tobas’ constitute fundamental input for their transformation into pedagogical resources for schools and teacher training programs.